Vulnerability and Robustness of Civil Infrastructure Systems to Hurricanes - Wang, Shuoqi; Reed, Dorothy A. (Frontiers in Built Environment, 2017)
Civil infrastructure systems play an important role in community resilience. Without proper functioning of the infrastructure, especially power delivery, society will not recover quickly from disruptive events such as hurricanes. In this paper, the vulnerability, response and recovery of selected infrastructure at the system level for several hurricanes in the USA are modeled using geo-statistical methods and employing post-event data. Inoperability is the main variable modeled for each infrastructure system. In this paper, robustness is a property considered to be the opposite of vulnerability and it plays an important role in the resiliency modeling. The infrastructure systems examined in this paper are electric power delivery and telecommunications. Connections among the systems are briefly explored.